An Analysis on the Place – Structure Relationship: Trabzon İçkale Mosque - Üstün Demirkaya, Fulya; Babul, Esra (ICONARCH International Congress of Architecture and Planning, 2017)
The abstract text urban spaces, which are part of change and transformation, constitute a whole made up of pieces shaped in line with the changing needs at different time periods. This study aims to shape the urban and social memory within the change/transformation dynamics based on the relationship between structure and location. Due to its geographical and geopolitical location, the province of Trabzon is one of the cities where the changing conditions can be tracked and target structure can be investigated in detail with all the urban structural features remaining within the city walls shaped by topographical conditions. With the conquest of the province in 1461, which was one of the most important breaking points in its history, the biggest church was converted into a mosque as a symbol of the conquest in accordance with the conquest traditions of the Ottoman Empire. The architectural representation of the changes made after this conquest based on a structure constructed by the Ottoman Empire was demonstrated in the construction of the mosque titled “Mescid-i Valide-i Merhum Sultan Abdullah” in the name of Sultan Abdullah commissioned by his mother Şirin Hatun in 1470. As understood from its name, this small mosque was commissioned during the term of office of Sultan Abdullah, son of Sultan Bayezid, as the governor of Trabzon in Yukarıhisar by his mother. It is thought that the first Muslim neighborhood in this province was formed around this small mosque along with Fatih Mosque, which was converted from a church into a mosque. Within this scope, the building made up of a small rectangle sanctuary comes to the forefront with its historical importance rather than its architectural style, besides the location where it was built. This monumental religious building, which was the expression of symbolic representation, was exposed to the risk of being destroyed for being among the “buildings having no architectural or artistic value” during the first years of the Republic, and it became a subject of discussion again with its transfer to another location within the scope of urban regeneration works while it was decided not to take its construction further in 2000. In this regard, it is aimed to handle the concept of “location” with which İç Kale Mosque was closely associated with, the importance of the location within the historical topography, and the traces it left in memories within the scope of the existing documents taking its symbolical value into account.